Participatory as everyday life: from creativity-based initiative to the production of networked space in Southeast Asian cities - Zaki Habibi (Department of Communications, Universitas Islam Indonesia, 2017)
The notion of creative city has been extensively discussed both in academic debate as well as public discourse, including on Asian context. However, a tendency to study only on strategic government policies in relation to this matter has led many multidimensional aspects being left behind. One of these important aspects is the creativity-based activities initiated and conducted by local groups, communities, or collectives on a daily basis apart from so-called the official city programmes. This paper that derives from participatory paradigm takes into account this kind of practice, and seek the meanings of participatory culture as everyday life in urban context. The participatory initiatives discussed inÂ this paper as the empirical cases are â€œTobucil & Klabsâ€ in Bandung, Indonesia and the street arts in George Town, Penang, Malaysia. Considering the current context that participation is getting more mediated (Livingstone, 2013), I employ digital ethnography and documentary photography as the methodological standpoints to understand the digital media practices â€“ i.e. online engagement â€“ that also intertwine with the offline engagement in these two particular cases. I argue, the creativity-based initiatives in these two Southeast Asian cities lead to new insight in understanding media and creativity in current Asia. Additionally, informed by the work of Henri Lefebvre on â€œsocial spaceâ€ and developed it further, I also argue that this certain participatory culture lead to the production of networked space in relation to city identities. This could contribute in forming a new theoretical model in understanding the interplay between media, participation, and urban cultures in digital era.Keywords: City identity, creativity; digital ethnography; digital media; documentary photography; everyday life; networked space; participation; Southeast Asia.